POWER PLAY IN THE CHURCH? THE CASE OF 1 TIMOTHY 2:8–15 - P.H.R van Houwelingen (STT Reformed Injili Internasional, 2019)
Thinking in terms of ecclesiastical power as a negative force has often found a breeding ground in the Pastoral Epistles. To what extent is that justified? This article examines a passage that always comes up when the position of women in the church is discussed: 1 Timothy 2:8−15. Three aspects will be considered consecutively: power, powerlessness, and authorised power. Power says something about the underlying problem that Timothy faced: the male/female relationship in the Ephesian congregation threatened to degenerate into a power struggle. Powerlessness refers to the story of Adam and Eve mentioned in verses 13−15. The Genesis narrative recounts human weakness, which in 1 Timothy becomes a sort of triptych about Eve and creation, Eve and the fall, and Eve and redemption. Authorised power is the way in which the problematic situation in Ephesus was regulated with apostolic authority, to create space for the trustworthy Word. Paul’s instructions about the behaviour of women could nowadays easily be considered a kind of misogynistic power play. However, the apostle should be interpreted on his own terms. This is true both for his social context and for his missionary drive. KEYWORDS: power, man, woman, congregation, Paul